PENINGKATAN KETERLIBATAN MAHASISWA DALAMPEMBELAJARAN BIOSTATISTIK DENGAN METODE KOOPERATIFMELALUI MEDIA LEMBAR KERJA MAHASISWA (LKM) DI PROGRAM STUDI PERUMAHSAKITAN - Murniati, Nia; Supriadi, Supriadi; Gunadi, Tri (Jurnal Vokasi Indonesia, 2013)
This research is motivated by the lack of passionate students of the Program Studi Perumahsakitan Vokasi in the following study courses Biostatistics, because the teaching method does not make the students become active and participate. Consequently Biostatistics courses often leave some students are forced to repeat the due credit limit does not reach the threshold value eventually pass (C) and of course is very detrimental to the student having to repeat the course credit until they intern (last semester). This study is a class act with the entire student subjects RS1 50 people Academic Year 2012/2013 in the University of Indonesia with the material limits of Biostatistics emphasis on material probability. Results were obtained in cycle 1 achieved an average score of 3770/5000 = 75.4, cycle 2 average scores achieved 4105/5000 = 82.1 and cycle 3 achieved an average score of 4585/5000 = 91.7. Conclusion The method of cooperative learning approach through the media LKM have a positive impact in improving student achievement is marked by an increase in the average scores achieved in each cycle, and through the media worksheet can increase student interest and motivation shown by increased activity in the classroom discussion. Advice is to carry out a cooperative approach through the media LKM method requires the preparation of a fairly mature, so the lecturer must be able to determine the learning scenario can actually be applied in order to obtain optimal results